Effect of NCO/OH on the Mechanical properties of Polyurethane Elastomers - .Mohammed, Malek M; ALJarrah, Mustafa M.; Abdul Lateef, Ahmed A. (Nahrain University College of Engineering Journal, 2008)
The present work is concerned with the preparation of polyurethane elastomers. Polyurethane elastomer was prepared by the bulk polymerization via one 4,4'diphenyl methane polypropylene glycol using stannous octeate as a catalyst. The operating conditions of the polymerization were studied and their affects on the mechanical properties of the prepared elastomer. with 4,4'diphenyl methane diisocyanate to equivalent of polypropylene glycol (NCO/OH)(1.5- 3), and curing temperature of about mechanical properties of polyuretha elastomers were: Kinetic of the reaction also was studied using adiabatic temperature rise method. The overall order of reaction was of the reaction was frequency coefficient of reaction ( (mole/g mixture)